Pengaruh Keputusan Investasi dan Leverage terhadap Kinerja Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Nur Aliza; Aminar Sutra Dewi (Lembaga Yasin AlSys, 2026)
Changes in economic conditions and industrial competition require manufacturing companies to maintain their financial performance through appropriate investment decisions and debt management. However, previous studies have shown mixed results regarding the effects of these two factors on corporate profitability. This study aimed to analyze the effects of investment decisions and leverage on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The study employed a quantitative approach with an explanatory design and panel data analysis. The sample consisted of 53 companies selected through purposive sampling, resulting in 265 observations. Data were collected from annual financial statements and analyzed using panel data regression with EViews 12. Investment decisions were proxied by the Price Earnings Ratio, leverage by the Debt to Equity Ratio, and financial performance by Return on Assets. The results showed that investment decisions had a negative and significant effect on financial performance, whereas leverage had a negative but insignificant effect. These findings broaden the understanding of signaling theory and financing structure by demonstrating that increases in investment and debt indicators are not always accompanied by increased profitability. This study emphasizes the importance of appropriate investment selection and debt management aligned with a company’s financial capacity to maintain sustainable financial performance.